Geometric Design of Coordinated Traffic Signal Intersections: Case Study of Four-Way Intersections at Kapuas II Bridge and Kapur Village - Zulkarnaen, Dedy; Mayuni, Siti; Mukti, Elsa Tri; Nurhayati, Nurhayati (Jurnal Teknik Sipil, 2024)
The four-way intersections at Kapuas Bridge II, Jalan Mayor Alianyang "“ Adisucipto (Intersection I), and Jalan Mayor Alianyang "“ Kapur Village (Intersection II) are connected by Kapuas Bridge II. According to the 2023 Indonesian Road Capacity Guidelines (PKJI), congestion at these two adjacent intersections can affect each other, necessitating coordinated solutions. The PKJI 2023 approach evaluates intersection performance, focusing on the Degree of Saturation and Delays. For optimal performance, intersections must meet minimum service levels. Intersections I and II have saturation levels of 1.08 and 1.15, respectively, and delays of 217 and 273 seconds, with a service level F, indicating delays exceeding 60 seconds. To meet PKJI standards, saturation should be below 0.85, which is not the case here. Improvements include widening approaches and optimizing green and cycle times. The first phase involves widening the north and south approaches to 8 meters and the east and west approaches to 7.5 meters, reducing the cycle time from 160 to 120 seconds. The final phase widens all approaches to 20 meters and sets the cycle time to 90 seconds.Keywords: APILL Intersection, Degree of Saturation, Delay, Service Level, Coordination of Intersection, Cycle Time